Upaya Pengembangan Usaha Pada UMKM Mebel Desa Nglebak Melalui Penerapan Digital Marketing - Kirana Aurelia Julianne Maharani; Naila Aisyah Putri; Yolanda Irfania; Mei Retno Adiwati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Group KKN-T MBKM UPN